Drug interaction between antiretrovirals and psychodrugs (Research, Society and Development, 2022)
Introduction: The human immunodeficiency virus type 1 (HIV-1) is the agent that produces AIDS, a disease recognized for more than forty years, which has reached pandemic proportions. Its origin dates back to the transmission to humans of retroviruses that infected populations of chimpanzees in central Africa approximately 100 years ago. From this location, its expansion to the whole world has been enormous, mainly in the last decades. Objectives: to carry out a literature review on the drug interaction between antiretrovirals and psychotropic drugs, identifying the factors that influence the consumption of psychotropic drugs in people with HIV. Method: Qualitative research, such as an integrative literature review, with data collected through articles available on online platforms. Results: The results obtained already published may be controversial, since some authors interpret certain adverse reactions as not resulting from drug interaction, but caused by the antidepressant, antipsychotic and antiretroviral drug itself, that is, the observation of effects side effects, which may be related both to the interaction of different classes of antiretrovirals and to that of antidepressants and antipsychotics with antiretrovirals, make it difficult to characterize the interaction and, therefore, this observation is often neglected. Conclusion: Despite the studies analyzed demonstrate effects between drug interactions (retrovirals and psychotropic drugs, research with a greater number of individuals should be developed.